APPROACH TO CHOICE A METHOD OF AID DIAGNOSTIC FOR INSTALLATION OF SOLAR AIR CONDITIONING - El-Amine, Ghernaout Med; Abdelkarim, Meghelli (European Scientific Journal, ESJ, 2013)
The building sector is one of the largest sectors of energy consumption. Heating, ventilating, and air conditioning - HVAC- is a critical component of any modern structure, from a ranch house to the tallest skyscraper. Typically, the energy that an HVAC system needs to work is directly drawn from the electric grid, But recently renewable energy offer other alternatives such as cooling with solar air conditioning which use the heat of the sun to reduce the energy needed to drive the cooling process of a conditioning system. This in turn, reduces the energy needed to run the compressor. The diagnosis is by definition, the identification of the cause of a failure by logical reasoning. In this light, our job is to cite the different methods of diagnosis, and make the best choice for a complex system of solar air conditioning following the characteristics desired and fixed.